Reassessment of the Dimensions and Layout of Roadside Canals - Irza Daffa Prawira; Prastowo Prastowo (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Until now, there have been puddles on several sections of the Grand Depok City Boulevard road, which are located in the Sukmajaya and Cilodong Districts. This study aims to review the drainage system at three inundation locations (A, B, and C), which includes layout, runoff discharge, channel design discharge, channel dimensions, culverts, and cost estimation. The results showed that the drainage system was built inadequately, so an outlet channel was needed at location A and culverts at locations A and C. The calculated runoff discharge ranged from 0.16-0.73 m3/second, with a planned channel discharge ranging from 0.38-1.10 m3/sec. With this discharge value, it is necessary to deepen the canal at location A, which was originally 0.5 m to 0.7 m, and to reduce the slope of the canal bottom at location B, which was originally 3% to 2%. The culverts required at location A are 18.5 m long and 0.6 m in diameter, and there are 39 at location C, each 8 m long and 0.2 m in diameter. The estimated total cost is IDR 155,492,000. Construction of canals and culverts should use precast concrete materials and be done at night. Keywords: Reviewing, Roadside channel, Runoff.